1933
DOI: 10.1037/h0069776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complete striate muscle paralysis upon the learning process.

Abstract: Psychology has long been vexed by a persistent controversy concerning the fundamental nature of the learning process. One group of psychologists has held to the intra-cerebral view that the trial-and-error process of learning is represented physiologically by a sort of 'battledore and shuttlecock' process which is limited entirely to the cerebrum. This theory is also implied in the writings of most physiologists and neurologists. Other psychologists have suggested a contrasting peripheral view, to the effect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
1

Year Published

1967
1967
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 14 publications
1
40
1
Order By: Relevance
“…Subsequent studies (e.g., Girden, 1940;Solomon & Turner, 1962) have challenged some of the conclusions drawn by Harlow and Stagner (1933). For example, Solomon and Turner demonstrated what when dogs were under the influence of curare they could learn to discriminate tones that were signals of subsequent shocks from tones that were never associated with shocks.…”
Section: Paralyzed Learningmentioning
confidence: 95%
See 1 more Smart Citation
“…Subsequent studies (e.g., Girden, 1940;Solomon & Turner, 1962) have challenged some of the conclusions drawn by Harlow and Stagner (1933). For example, Solomon and Turner demonstrated what when dogs were under the influence of curare they could learn to discriminate tones that were signals of subsequent shocks from tones that were never associated with shocks.…”
Section: Paralyzed Learningmentioning
confidence: 95%
“…Harlow and Stagner (1933) called theories in which such a response was mandatory peripheral, and theories in which such a response was not necessary intra-cerebral. They conducted a number of experiments in which cats and dogs were conditioned when under the influence of curare.…”
Section: Paralyzed Learningmentioning
confidence: 99%
“…Research with infrahuman Ss has demonstrated rather consistently the conditionability of the autonomically regulated pupillary reflex (Gerall & Obrist, 1962;Girden, 1942;Harlow, 1940;Harlow & Stagner, 1933). On the other hand, studies with adult human Ss have failed to provide clear evidence of pupillary reflex conditionability.…”
mentioning
confidence: 92%
“…Table 1 summarizes classic response-prevention studies, most of them reviewed by Solomon and Turner (1962). An early, relatively large study by Harlow and Stagner (1933) failed to demonstrate CR acquisition when CS-US experiences were given to animals paralyzed by curare, seemingly supporting the notion that CR performance is necessary for acquisition. However, in a remarkable series of studies, Girden established the following: 1) under curare, muscular contractions can be produced, although they are minimal and often do not cause overt movements; 2) these contractions can be conditioned similarly to normal contractions; 3) contractions conditioned under curare disappear once the animal recovers, but reappear if it is again drugged (Girden, 1940(Girden, , 1942(Girden, , 1947Girden & Culler, 1937).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a remarkable series of studies, Girden established the following: 1) under curare, muscular contractions can be produced, although they are minimal and often do not cause overt movements; 2) these contractions can be conditioned similarly to normal contractions; 3) contractions conditioned under curare disappear once the animal recovers, but reappear if it is again drugged (Girden, 1940(Girden, , 1942(Girden, , 1947Girden & Culler, 1937). Given these findings, Harlow and Stagner's (1933) failure came to be attributed to drugged animals performing different CRs than non-drugged animals, rather than no CRs, and the original question remained unsettled. Solomon and Turner (1962) and Leaf (1964) attempted to make progress by using d-tubocurarine, a curare variety unavailable to Girden that was not expected to impair transfer between the drugged and non-drugged states (based on reports from brave human volunteers: Prescott, Organe, & Rowbotham, 1946;Smith, Brown, Toman, & Goodman, 1947).…”
Section: Introductionmentioning
confidence: 99%